Applying organizational density to local public service performance: separating homeless service outcomes from outputs. Issue 2 (1st February 2023) - Sullivan, Andrew; Kim, Saerim; Lee, David
ABSTRACT: What happens to local services' performance when service-provider density increases in a community? The answer is difficult. To explore how density relates to multiple aspects of performance, this study aims to examine the effects of service-providers' density on service outputs and policy outcomes. Using a panel dataset of local homeless service planning bodies, the Continuum of Care Programme, we found that service outputs improved; however, the prevalence of homelessness did not decrease. Drawing upon organizational density theory, our findings contribute to the extant knowledge on public management by exploring how service-provider density relates to service outputs and policy outcomes separately.